Tata Kelola Keuangan pada TK Aisyiyah Bustanul Athfal Lhong Raya, Banda Aceh - Aini, Zahriatul; Amalia, Cut Intan; Puspita, Desy; Sufika, Arwina; Agustina; Mirnawati; H, Khairita; Azlina; Akbar, Indra; Meysinta, Desti Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
The financial management training at TK Bustanul Athfal Lhong Raya aims to enhance the capacity of the school administrators in managing finances transparently and accountably. The issues faced by the administrators include a lack of skills in structuring financial documents and limited use of technology. This training involved the school principal, treasurer, teachers, and representatives from the school committee as participants, covering topics such as budgeting, cash flow recording, and the preparation of simple financial reports. The methods combined theory and practice to ensure participants could implement what they learned in their daily activities. The results showed a significant improvement in participants' understanding and skills in managing financial documents in a more structured and transparent manner, as evidenced by their ability to create daily cash books, annual budgets, and more systematic financial reports. Post-training monitoring confirmed that most participants had applied the taught materials in managing school finances, although further assistance is required, especially in the use of financial technology. This activity successfully established a better financial management system, increased transparency, and built trust among the community in the financial management of TK Bustanul Athfal. This training provides a strong foundation for accountable and sustainable financial management in TK Bustanul Athfal Lhong Raya Banda Aceh.